2021
DOI: 10.1111/acem.14264
|View full text |Cite
|
Sign up to set email alerts
|

Meeting unique requirements: Community consultation and public disclosure for research in emergency setting using exception from informed consent

Abstract: Background Exception from informed consent (EFIC) regulations for research in emergency settings contain unique requirements for community consultation and public disclosure. These requirements address ethical challenges intrinsic to this research context. Multiple approaches have evolved to accomplish these activities that may reflect and advance different aims. This scoping review was designed to identify areas of consensus and lingering uncertainty in the literature. Methods Scoping review methodology was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 78 publications
(151 reference statements)
0
20
0
Order By: Relevance
“…In addition to the requirements above, additional special protections are afforded to persons unable to exercise their autonomy in deciding whether to participate in the trial 17 . These include: (1) community consultation, a process that provides the opportunity for discussions with and soliciting meaningful input from the community in which the study will take place and from which study subjects will be drawn 17–20 ; (2) public disclosure, a process by which information about the research and its results are disseminated to the affected communities 17,21 ; and (3) the requirement that there be a time‐limited effort to contact an LAR to give consent with appropriate documentation, or decline participation, and the opportunity for family members who are not LARs to opt out on behalf of the patient 17…”
Section: The Exception From Informed Consent Requirements For Emergen...mentioning
confidence: 99%
“…In addition to the requirements above, additional special protections are afforded to persons unable to exercise their autonomy in deciding whether to participate in the trial 17 . These include: (1) community consultation, a process that provides the opportunity for discussions with and soliciting meaningful input from the community in which the study will take place and from which study subjects will be drawn 17–20 ; (2) public disclosure, a process by which information about the research and its results are disseminated to the affected communities 17,21 ; and (3) the requirement that there be a time‐limited effort to contact an LAR to give consent with appropriate documentation, or decline participation, and the opportunity for family members who are not LARs to opt out on behalf of the patient 17…”
Section: The Exception From Informed Consent Requirements For Emergen...mentioning
confidence: 99%
“…Fins and colleagues describe an approach of “consensus consent” when considering enrolling persons with DoC in clinical trials, which requires involvement and agreement among four parties—the participant’s “legally authorized representative, the subject’s physician, the clinical investigator, and a lay subject advocate” [ 101 , 102 , 103 ]. Others contend that a model of interactive community consultation or public deliberation, whereby salient values and preferences of recovered patients and other key stakeholder groups are ascertained in advance of a planned study, could potentially supplant or supplement the traditional informed consent process in select circumstances [ 81 , 104 , 105 , 106 , 107 ]. Despite the proliferation of alternative models to informed consent, ethical debate still exists regarding the optimal form these approaches should take.…”
Section: Preserving Patient Autonomy In Clinical Trials Involving Per...mentioning
confidence: 99%
“…A recent review by Dickert et al 4 found that CC traditionally involved either interactive, discussion-based activities, such as town hall meetings, existing support group meetings, and in-person interviews or focus groups; or noninteractive, survey-based activities, such as random digit dialing telephone surveys, or web-based surveys. The PD methods, in contrast, typically included press releases; radio, TV, and public service announcements; social media advertisements; websites; individual communication; in-person disclosure; posters and brochures in hospitals; and meetings.…”
Section: Traditional Approaches To CC and Pdmentioning
confidence: 99%
“…The PD methods, in contrast, typically included press releases; radio, TV, and public service announcements; social media advertisements; websites; individual communication; in-person disclosure; posters and brochures in hospitals; and meetings. The authors highlighted the clear conceptual distinction between CC and PD, whereas in practice, there is some overlap 4 . Both CC and PD involve the unidirectional provision of information, whereas only CC involves consultation—or bidirectional flow of information—between community members and investigators 4 .…”
Section: Traditional Approaches To CC and Pdmentioning
confidence: 99%
See 1 more Smart Citation